Catalytic asymmetric synthesis of (+)-anthecotulide using enyne and Meyer-Schuster rearrangements. - Hodgson, D; Talbot, E; Clark, B (2011)
The bioactive sesquiterpene lactone (+)-anthecotulide (1) is synthesized for the first time, in a six-step sequence devoid of protecting groups. The key transformations are a novel Rh(I)-catalyzed asymmetric enyne rearrangement of a terminal alkynyl ester (4), to form the α-methylene-γ-butyrolactone core, and a final-step mild Au(I)-catalyzed Meyer-Schuster rearrangement.